2022
DOI: 10.1007/s00018-022-04325-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial matrix-localized Src kinase regulates mitochondrial morphology

Abstract: The architecture of mitochondria adapts to physiological contexts: while mitochondrial fragmentation is usually associated to quality control and cell death, mitochondrial elongation often enhances cell survival during stress. Understanding how these events are regulated is important to elucidate how mitochondrial dynamics control cell fate. Here, we show that the tyrosine kinase Src regulates mitochondrial morphology. Deletion of Src increased mitochondrial size and reduced cellular respiration independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Additionally, Src and FAK-activated STAT3 can directly interact with mitochondria to stimulate OXPHOS activity. (Visavadiya et al, 2016, Djeungoue-Petga et al, 2019, Guedouari et al, 2021, Guedouari et al, 2020, Lurette et al, 2022). In contrast, our results show that actin polymerization downstream of these signalling events is required to modulate mitochondrial structure in response to ECM cues in mammospheres.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, Src and FAK-activated STAT3 can directly interact with mitochondria to stimulate OXPHOS activity. (Visavadiya et al, 2016, Djeungoue-Petga et al, 2019, Guedouari et al, 2021, Guedouari et al, 2020, Lurette et al, 2022). In contrast, our results show that actin polymerization downstream of these signalling events is required to modulate mitochondrial structure in response to ECM cues in mammospheres.…”
Section: Discussionmentioning
confidence: 98%
“…Common mitochondrial dysfunction includes increased ROS production, decreased ATP content due to oxidative phosphorylation, decreased mtDNA biosynthesis, abnormal mitochondrial morphological fusion and division imbalance, autophagy damage, etc. [ 23 ]. MtDNA is an independent double stranded DNA, which is more susceptible to ROS attacks due to the lack of DNA repair enzymes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the NTM stage is separated from the TM stage by only 8 h [ 47 ], the rapid change in mitochondrial density during florescence indicated that mitochondria underwent fission during this interval. Recent studies showed that mitochondrial elongation enhances cell survival, by increasing respiration to support physical activity [ 48 ], and that the transient and rapid morphological adaptations of mitochondria are crucial for many cellular processes, such as the cell cycle, immunity, apoptosis, and mitochondrial quality control [ 49 ]. In addition, a comparative analysis of TM skunk cabbage with NTM potato and cauliflower showed increased mitochondrial and metabolic activity in skunk cabbage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%